Management of Teacher Work Stress at Madrasah Tsanawiyah Al-Ikhlas Sukobubuk - Tsuroya, Nabeela Himmatus; Almafahir, Ahmad; Wahid, Abdul (QUALITY, 2024)
Teacher work stress is an increasingly worrying phenomenon in education, especially in rural educational institutions. This research aims to analyze teacher work stress management at MTs Al-Ikhlas Sukobubuk, focusing on identifying causal factors, manifestations, and efforts to minimize work stress. Using a qualitative approach, this study involved the principal and five teachers selected through purposive sampling. Data was collected through structured observation, in-depth interviews, and documentation, then analyzed using the Miles & Huberman method. The results revealed five main factors causing work stress: excessive workload, unfavorable madrasa climate, compensation mismatch, hierarchical pressure, and inadequate investment in professionalism. Manifestations of stress include emotional symptoms, fatigue, cardiovascular, gastrointestinal, and behavioral changes. Efforts to minimize stress include improving time management, strengthening communication, building supportive relationships, and maintaining physical and mental health. This research concludes the importance of a holistic approach to teacher work stress management to improve the quality of education.